2016
DOI: 10.1039/c6cc03318k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a highly active oxidation catalyst with improved distribution of titanium coordination states

Abstract: A facile strategy is proposed to construct a highly active oxidation catalyst with optimally distributed titanium coordination states containing "TiO4" and "TiO6" species. The "TiO6" species in TS-1(+) shows a superior catalytic oxidation activity, which is 2-3 times that of "TiO4" species in TS-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 37 publications
1
63
0
Order By: Relevance
“…There were two peaks located at the 2 θ of 24.4° in the H−S‐1 whereas there are unimodal peaks in microporous m‐TS‐1, H−S‐1@TS‐1 and M‐m‐TS‐1, indicating the coverage of the monoclinic syngony of silicalite‐1 by the orthorhombic syngony of TS‐1. This is an indirect proof for the insertion of titanium to the framewok ,…”
Section: Methodsmentioning
confidence: 78%
“…There were two peaks located at the 2 θ of 24.4° in the H−S‐1 whereas there are unimodal peaks in microporous m‐TS‐1, H−S‐1@TS‐1 and M‐m‐TS‐1, indicating the coverage of the monoclinic syngony of silicalite‐1 by the orthorhombic syngony of TS‐1. This is an indirect proof for the insertion of titanium to the framewok ,…”
Section: Methodsmentioning
confidence: 78%
“…This band is also present in the MFI TS‐1B material, synthesized by Balducci et al . or TS‐1+ zeolite synthesized by L. Wu et al . It was suggested by Wu et al .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, considering the possibility of modifying Ti-MWW with respect to both the structure and microenvironment of Ti active sites, Ti-MWW was further studied. The PI-assisted arrangement has been reported to be an effective way to enhance the catalytic performance of Ti-MWW zeolites in the epoxidation reactions of alkenes (Wu et al, 2016). Thus, in the present case of cyclopentene, PIassisted structural modification was also performed.…”
Section: A Comparison Of the Catalytic Performance Over A Series Of Tmentioning
confidence: 98%
“…Xu et al (2020) reported the one-step rapid synthesis of TS-1 with mononuclear TiO 6 species affording a high turnover number value of 272 in the 1-hexene epoxidation reaction. Wu et al (2016) illustrated that the mononuclear "TiO 6 " species showed the catalytic activity 2-3 times that of the "TiO 4 " species in TS-1 for the epoxidation of alkenes.…”
Section: Introductionmentioning
confidence: 99%